Phenotypic Antimicrobial Susceptibility and Genotypic Characterization of Clinical Ureaplasma Isolates Circulating in Shanghai, China - Ma, Hongxia; Zhang, Xuemei; Shi, Xiaoxing; Zhang, Jun; Zhou, Yunheng (Frontiers in Microbiology, 2021)
There is a growing global concern regarding the rise of antimicrobial resistance among Ureaplasma spp. isolates. However, studies on the antimicrobial susceptibility profiles, resistance mechanisms, and clonality of Ureaplasma spp. clinical isolates are still limited and cover only some geographic regions. Firstly, Ureaplasma species from the urogenital tracts of patients in Shanghai, China were isolated by using the culture medium (A8 and 10B broth), and identified the genotype by polymerase chain reaction (PCR). Secondly, the antimicrobial susceptibility tests were determined by using broth microdilution assay. Then, the resistance genetic determinants to fluoroquinolones (FQs), macrolides, and tetracyclines were investigated through PCR/DNA sequencing. Finally, the molecular epidemiology of Ureaplasma species was studied by multilocus sequence typing (MLST). Among 258 isolates, Ureaplasma parvum (UPA) and Ureaplasma urealyticum (UUR) were found in 226 (87.60%) and 32 (12.40%) isolates, respectively. The minimum inhibitory concentrations (MICs) of 258 Ureaplasma spp. strains ranged from 0.015 to 64 µg/mL for all 11 kinds of antimicrobials. Regardless of species, the isolates were most sensitive to AZI (1.94%), JOS(3.49%), and CLA(4.23%). Among them, there were 39 (15.12%) multidrug-resistant (MDR) strains, including 32 UPA isolates. The resistance rates of UPA to CIP (91.59%), LEV (73.89%), and ROX (36.28%) were significantly higher than those of UUR. 26 FQ-resistant isolates had amino acid substitutions in gyrA and in parC (Ser83Leu). Mutations were detected in genes encoding ribosomal proteins L4 (Thr84Ile) and L22 (Ser81Pro) in macrolide-resistant isolates. Tet(M) was found in four UPA isolates. These mutations were mainly found in UPA isolates. Sequence type 1 (ST1) was the predominant ST, which contained 18 isolates. In conclusion, this study showed a higher resistance rate (especially to ERY, ROX, and LEV), higher substitution rate, and higher MDR rate among UPA strains. The most active antimicrobial agents were AZI, JOS, and CLA. Identifying UPA or UUR in clinical isolates could help clinicians to choose appropriate drugs for treatment. The main resistance mechanisms may involve gene substitution of Ser83Leu in parC and Ser81Pro in L22. ST1 was the predominant ST of Ureaplasma isolates with MDR to FQs and macrolides in Shanghai, China.